Collaborative 3D real modeling by multi-view images photogrammetry and laser scanning: The case study of Tangwei Village, China. (June 2021) - Hu, Yinglong; Chen, Xinxiang; Tang, Zixin; Yu, Jian; Chen, Yingbiao; Wu, Zhifeng; Yang, Dexiao; Chen, Yongming
Abstract: Cultural heritage has extremely high historical significance and architectural aesthetic value. However, at present, the protection of many cultural heritage is facing great challenges, and it is urgent to get a complete and authentic record for preserving the memory of cultural heritage and the civilization it carries. The 3D real model can simultaneously record and express the geometric appearance and texture image information in the same 3D scene, which is one of the most comprehensive document types for recording the physical appearance authentic information of cultural heritage. Based on mature photogrammetry, aerial triangulation and computer vision technologies, a technology workflow for collaborative modeling for cultural heritage by multi-source data is proposed in this paper. Acquiring UAV low-altitude multi-view images, ground multi-view images and 3D laser point clouds data to record the appearance information of cultural heritage, the workflow through a series of technical processing processes to connect and integrated these data and their analysis results to generate a complete, detailed and high-resolution 3D real model, which is beneficial for overcoming a series of problems caused by the lack of sufficient ground information in the traditional technology workflow.